Developing Historical Consciousness and a Community of History Practitioners: A Survey of Prospective History Teachers Across Canada - Lévesque, Stéphane; Zanazanian, Paul (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2015)
This paper looks at the historical consciousness of prospective history teachers in Canada. Using a bilingual online survey instrument inspired by the pan-Canadian research Canadians and their Pasts with volunteer participants (N=233), the study investigates their background knowledge, their perceptions of the trustworthiness of sources, their experiences in the history classroom, and their visions of school history. Results reveal that few prospective teachers have extensive knowledge of Canadian history and limited experience with active, inquiry-based teaching approaches to the past. However, a majority of them have very strong conceptions and sense of purposes regarding school history. The paper discusses the implications of this study, notably the need for professional communities of history practitioners.